Prehabilitation and nutritional interventions - an interdisciplinary perspective - Alicja Zdankiewicz; Wiktoria Konaszczuk; Piotr Pawłowski; Aneta Kościołek (Kazimierz Wielki University, 2022)
Introduction: Nutrition is defined as the acquisition of exogenous nutrients. It is a basic need of a living organism. Malnutrition has become a problem for hospitalized patients, especially in the surgical ward. The condition leads to the deterioration of the patient's clinical performance and quality of life. Ongoing nursing interventions, particularly the use of parenteral or enteral nutrition, can reduce the risk of complications resulting from the inadequate nutrient supply.  Aim of the study: The purpose of this study is to analyze nutritional problems in the practice of a surgical nurse.  Material and method: A non-systematic review of the available literature on nutritional problems published in the last seven years (2015 - 2022) was conducted. Databases such as Google Scholar and PubMed were searched, using the following keywords: nutritional problems, malnutrition, nutritional treatment, surgical nursing, and hospital malnutrition.  Sixteen original and review papers were eligible for analysis. The criteria for qualifying articles for review were title, abstract content, keywords, and topics related to nutrition problems in the context of nursing practice.  Results and conclusions: Malnutrition is a serious problem in clinical practice.  Standardized scales NRS 2002, MUST, and MNA are used to correctly diagnose this problem. The nurse's role in caring for a patient with a nutritional deficit is to monitor the patient's condition, take anthropometric measurements and collect materials for diagnostic tests. This allows the correct selection of nutritional treatment individually for the patient.